ANALISIS PENGARUH BANTUAN SOSIAL PEMERINTAH DAN LITERASI KEUANGAN TERHADAP MAHASISWA YANG TERDAMPAK COVID-19 - Dwi Urip Wardoyo; Furqan Ramadhan; Brilyan Yusuf Akbar; Gilang Ramadhan; Muhammad Fariz Fahreza; Wahid Prasetyo Nugroho (Pusat Riset dan Inovasi Nasional, 2023)
This Studies aims to examine the analysis of the effect of government social assistance and financial literacy on students affected by COVID-19. This research is a policy research. The method used in this research is descriptive qualitative with evaluative data and literature studies. In this study, literature was obtained from information that developed in the news related to the distribution of government social assistance and financial literacy information circulating among Telkom University students affected by Covid-19.